Web Block Craft: web development for children using Google Blockly - Gunaratne, Madhumini; Weerasekara, Senal; Weerakkody, Dehemi; Sashmitha, Nisal; Zoysa, Rivoni De; Kodagoda, Nuwan (International Journal of Electrical and Computer Engineering (IJECE), 2024)
Web Block Craft is an innovative educational application that uses the Google Blockly framework to teach web development to children aged eleven and above. The application serves as a comprehensive learning tool, allowing users to explore both frontend project and backend project development. The frontend project includes HTML, CSS, JavaScript, and DOM manipulation, while the backend project covers server building, web app security, application programming interfaces (APIs), and database management. Web Block Craft's unique block-based interface allows users to easily drag and drop components into a dynamic working environment, resulting in an engaging experience with live output display and simultaneous code presentation. A unique feature of Web Block Craft is the integration of a platform within the application, which allows teachers to create lessons with step-by-step instructions for students. This new feature allows for a more structured learning experience, which improves understanding of web development concepts. To enhance the learning experience, the application provides extensive documentation, serving as a valuable resource for users to grasp the intricacies of web programming. By combining the power of Google Blockly with a creative user interface and educational resources, Web Block Craft provides a comprehensive learning environment that empowers creative web programming with confidence.